Identification of Family Members Gobiidae in the Mangrove Forest Nature Reserve on the East Coast of Jambi Province - Rosalia, Ipana; Nugraha, Anggit Prima; Setiyaningrum, Dewi Aswin; Uljannah, Lulu’ (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Jambi Province has abundant natural resources, including mangrove forests that serve as habitats for various animal species. This study aimed to increase understanding of conservation and to identify types of mudskippers and the characteristics of their habitats in the East Coast Mangrove Forest Reserve. The research used purposive sampling at three different spots: residential areas, rivers, and mangrove zones. The study found two fish species (Boleophthalmus boddarti and Periophthalmodon schlosseri) each found in different areas depending on their preferred habitats. In conclusion, each type of habitat supports the growth of mudskippers, and it's recommended that the mangrove area’s sustainability continues to be protected.